2013
DOI: 10.1080/17452007.2013.775102
|View full text |Cite
|
Sign up to set email alerts
|

Can virtual workspaces enhance team communication and collaboration in design review meetings?

Abstract: The development of software to facilitate collaborative working among project teams has been an active research area for the last two decades. However, the recent impetus in deploying BIM in construction has brought teamwork to the forefront and, therefore, it is important to conduct an in-depth study as to how BIM could be complemented with advances in visualisation and interaction technology to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Earlier work furthermore demonstrated that more introverted persons are more comfortable with the possibility to give feedback individually . In line with that, Bassanino, Fernando, and Wu (2014) conclude that the possibility to evaluate a design proposal on one's own screen provides users privacy, which may encourage clients' willingness and confidence to collaborate with designers. Based on this, we expect that:…”
Section: Participation In Solution-findingsupporting
confidence: 52%
“…Earlier work furthermore demonstrated that more introverted persons are more comfortable with the possibility to give feedback individually . In line with that, Bassanino, Fernando, and Wu (2014) conclude that the possibility to evaluate a design proposal on one's own screen provides users privacy, which may encourage clients' willingness and confidence to collaborate with designers. Based on this, we expect that:…”
Section: Participation In Solution-findingsupporting
confidence: 52%
“…Moreover, these studies show the importance of establishing social presence for multiple users involved in collaborative tasks to achieve common goals (Wienrich et al 2018). And while they can be difficult to coordinate, co-located or face-to-face sessions have advantages over remote alternatives for their greater communication channel "bandwidth" (Bassanino et al 2014), in which non-verbal cues and gesture-driven communication are key in mutual engagement as indirect measurements of social presence (Germani et al 2012). The importance of social presence is supported by studies that examine the socio-emotional dimensions of human communication in collaborative problem solving tasks.…”
Section: Vr In Design and Constructionmentioning
confidence: 99%
“…pointing, gesturing, moving). This aspect of reviewing design projects in collaborative VR environments can foster more complex group interactions and faster decision-making abilities (Bassanino et al 2014;Sallnäs 2005). At the same time, the informal nature of the observed sessions (i.e.…”
Section: Fig 12: Conceptual Representation Of Time the Users May Spementioning
confidence: 99%
“…In essence, implementing BIM in an environment where effective collaboration is absent is "scratching the surface" (Mignone et al, 2016). To address this, investigators have identified a wide range of problems that hinder establishing a collaborative environment in BIMCPs (Bassanino, Fernando and Wu, 2014;Mignone et al, 2016). Of these, Olatunji (2011b) contended that the conventional legal structure on construction projects is a barrier to collaborative attempts in BIMCPs.…”
Section: Collaboration On Bim-enabled Construction Projectsmentioning
confidence: 99%
“…The technical capabilities of BIM in facilitating a collaborative environment has been promoted as a selling point for BIM methodology (Alreshidi, Mourshed and Rezgui, 2016;Liu, van Nederveen and Hertogh, 2016). Gaining the full benefits offered by BIM methodology is contingent upon effective collaboration and coordination of activities in BIMCPs (Alreshidi, Mourshed and Rezgui, 2016;Bassanino, Fernando and Wu, 2014;Volk, Stengel and Schultmann, 2014). In essence, implementing BIM in an environment where effective collaboration is absent is "scratching the surface" (Mignone et al, 2016).…”
Section: Collaboration On Bim-enabled Construction Projectsmentioning
confidence: 99%